2018
DOI: 10.1016/j.jvs.2017.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan attenuates angiotensin II-induced abdominal aortic aneurysms through the inhibition of c-Jun N-terminal kinase and nuclear factor κB activation

Abstract: Fucoidan inhibits the progression of experimental AAA growth through the attenuation of proinflammatory nuclear factor κB and c-Jun N-terminal kinase activation. Fucoidan could be a potential medical adjunctive therapy for small AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…In this study, we highlight 4-HNE and ROS production as a vicious cycle in heatstroke-induced ALI and the roles of ALDH2 in breaking the vicious cycle. Activation of NF-κB-induced NOXs activation and ROS production ( 34 , 49 , 50 ). Previous studies indicated that 4-HNE increased the production of ROS through NOX and 5-lipoxygenase (5-LO) ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we highlight 4-HNE and ROS production as a vicious cycle in heatstroke-induced ALI and the roles of ALDH2 in breaking the vicious cycle. Activation of NF-κB-induced NOXs activation and ROS production ( 34 , 49 , 50 ). Previous studies indicated that 4-HNE increased the production of ROS through NOX and 5-lipoxygenase (5-LO) ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Inflammatory factors, oxidative stress, and matrix metalloproteinases (MMPs) are enriched in the aneurysmal vascular wall. [ 23 , 24 ] High levels of alcohol have been shown to upregulate MMPs in the aorta and kidneys in rats. [ 25 , 26 ] The associations between alcohol consumption and doses and the incidence of AAA are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…AngII‐induced AAA formation in ApoE ‐/‐ mouse has become the most widely used animal model (Daugherty et al, ; Tsai et al, ). Hence, we evaluated the role of LA in AAA formation by using Ang II‐treated ApoE ‐/‐ mice.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were randomly divided into four groups (n = 12 per/group): Control, AngII, AngII+LA5, and AngII+LA10. AAA models were established in the last three groups, as previously described (Tsai et al, 2017). Briefly, after anesthetizing with 50 mg/kg of pentobarbital sodium, the mice were given 1,000 ng/kg/min of AngII (Sigma-Aldrich, St. Louis, MO) via implantation with subcutaneous osmotic mini-pumps for 4 weeks.…”
mentioning
confidence: 99%